Insights from the in silico structural, functional and phylogenetic characterization of canine lysyl oxidase protein - Afnan Saleem; Shiveeli Rajput (Journal of Genetic Engineering and Biotechnology, 2020)
Abstract Background Lysyl oxidase is an extracellular regulatory enzyme with an imperative role in interlinking of collagen and elastin by oxidizing lysine residues. Lysyl oxidase has been implicated in incidence of mammary tumors in bitches. Therefore, it becomes significant to study the structural and functional features of this enzyme for a better understanding of its molecular mechanisms. Results The detailed computational investigation of the canine lysyl oxidase protein was analyzed in silico with respect to its physicochemical properties, secondary and tertiary structure predictions and functional analysis using standard bioinformatic tools. Lysyl oxidase is a flexible protein with an average molecular weight of around 46 kDa, unstable, hydrophilic, and extracellular (secretory) in nature. Twelve cysteine residues and a disulfide bridge were also found. Secondary structure analysis shows that most of the protein has predominant coiled configuration. A putative copper-binding region signature was predicted. The phylogenetic relationship of canine lysyl oxidase with a vast range of mammalian species indicates that the protein was very well conserved throughout the course of evolution. Top 10 interacting proteins were identified using STRING v10.0 analysis, elastin being the closest interacting protein. Functional analysis by InterproScan predicted protein’s biological role in oxidation-reduction process. Conclusion Understanding the structural and functional properties of the protein will facilitate a better understanding of its mechanism of enzyme action. Further, the predicted 3D model will serve as a cornerstone for further understanding towards the tumorigenesis potential of the protein.